2003
DOI: 10.1007/s00417-003-0781-y
|View full text |Cite
|
Sign up to set email alerts
|

Melanocortins applied intravitreally delay retinal dystrophy in Royal College of Surgeons rats

Abstract: This study is the first to demonstrate that: (1) intravitreally injected MA promotes a dose-related localized rescue of photoreceptors in RCS retinae which may be related to the hormone's neurotrophic activity; (2) MA has no mitogenic or angiogenic properties; (3) MA, as a neuroprotective agent, might be considered for future treatment of retinal dystrophy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
15
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 32 publications
1
15
0
Order By: Relevance
“…For example, α-MSH suppresses inflammation and maintains an intact retina in infectious [20] and autoimmune [21] uveitis, respectively. Intravitreal injection of an α-MSH analog protects photoreceptor cells from death in a rat model of retinal dystrophy in a dose-dependent manner [22]. It is also notable that α-MSH suppresses the oxidative stress induced by ultraviolet radiation in skin keratinocytes and melanocytes via the MC1R-mediated cAMP-PKA pathway, independent of melanin genesis [23][25].…”
Section: Introductionmentioning
confidence: 99%
“…For example, α-MSH suppresses inflammation and maintains an intact retina in infectious [20] and autoimmune [21] uveitis, respectively. Intravitreal injection of an α-MSH analog protects photoreceptor cells from death in a rat model of retinal dystrophy in a dose-dependent manner [22]. It is also notable that α-MSH suppresses the oxidative stress induced by ultraviolet radiation in skin keratinocytes and melanocytes via the MC1R-mediated cAMP-PKA pathway, independent of melanin genesis [23][25].…”
Section: Introductionmentioning
confidence: 99%
“…Intravitreal injection of α-MSH analogs retard photoreceptor loss in RCS rat, which is a model of retinal dystrophy. 71 This may be working through the melanocortin receptors inducing some undefined neurotropic activity. It has also been demonstrated that topical application of α-MSH is effective in lowering the intraocular pressure in normal tension rabbits for up to six hours by stimulating PGE2 and prostacyclin levels in iris and ciliary body cells.…”
Section: Application Of α-Msh In Ocular Therapymentioning
confidence: 99%
“…Taylor et al find αMSH is a post-caspase suppressor of apoptosis in macrophages [14]. Intravitreal injection of an αMSH analog protects photoreceptor cells from death in a rat model of retinal dystrophy in a dose-dependent manner [15]. However, few literatures were found in the study of αMSH in adipocyte apoptosis and the regulatory mechanism in the process.…”
Section: Introductionmentioning
confidence: 99%